ANALYSIS AND DESIGN OF MRT’S CIRCULAR TU - Bagus Prayoga; Sumarman Sumarman*; Ingrid Multi Rezeki (FAKULTAS TEKNNIK UNIVERSITAS SWADAYA GUNUNG JATI, 2018)
ABSTRACTJakarta MRT was one of solution to solve the traffic jam in Jakarta. There are two physical constructions which serves as the main infrastructure of Jakarta MRT, elevated and underground track. It is not only the first MRT in Indonesia but also, the first large-scale underground works in Jakarta. The physical construction of underground structure became an interesting case to be researched. The use of precast concrete tunnel lining (PCTL) segment was necessary to hold the loads and to provide the space for underground track.In designing the tunnel lining, calculation of the member forces and safety check are necessary to determine the amount of rebar and the dimension, and also to know the value of safety, so, the tunnel lining can be used as the function. According to the guidelines for the design of shield tunnel lining issued by International Tunnelling Association (ITA, 2000), the member forces of tunnel lining could be calculated by (1) Elastic Equation Method, (2) Bedded Frame Method, (3) Finite Element Method (FEM). In this research, the member forces of tunnel lining are calculated using analytical method, without computer program. Therefore, method (1) is used to know the value of each member forces to be used for designing the reinforcement bars. The member forces are analysed for tunnel lining with 6.8 m outer diameters, 1.5 m width and 0.25 m thickness in Jakarta MRT CP106 (Bundaran HI).Based on research which has been done, obtained the maximum values for positive bending moment in the tunnel crown (θ = 0°) is 101.352 kN.m, for negative bending moment in the tunnel axis (θ = 90°) is -281.394 kN.m. In contrary, the value of maximum axial force is in the tunnel axis (θ = 90°) is 1094.538 kN, for minimum axial force is in the tunnel crown (θ = 0°) is 904.674 kN. While, the value of maximum shear force is in (θ = 120°) is 118.740 kN, for minimum shear force is in (θ = 30°) is -66.866 kN. The result of safety checks against member forces in tunnel lining, the value of nominal bending moment multiplied by reduction factor (ϕ · Mn) is 296.263 kN.m, bigger than the value of ultimate bending moment (Mu) is 281.394 kN.m. For the value of nominal shear force multiplied by reduction factor (ϕ · Vn) is 136.095 kN, bigger than the value of ultimate shear force (Vu) is 118.740 kN. While, safety check against thrust force of shield jack obtained the value of maximum compressive stress of concrete segment (????????) is 5.016 MN/m2, bigger than the value of allowable stress (????????????) is 16 MN/m2.Keywords: Jakarta MRT, underground, tunnel lining, member forces, Elastic Equation Method.